PROBLEMS IN THE ORGANISATION OF THE TRANSPORT PROCESS ON THE INTERNATIONAL MARKET - Iwona KRZYŻEWSKA (Scientific Journal of Silesian University of Technology. Series Transport)
The transport process consists of many stages, where many interferences and problems may occur. It is important to identify these problems and find solutions to them, for example, using innovative tools supporting transport process management. A properly organised transport process allows the entire supply chain to function properly. For a transport process to be effective, it must be appropriately coordinated from planning, organising, implementing and controlling. In each of these phases, different types of problems may be encountered; therefore, the persons responsible for the various phases must monitor them closely. By reacting quickly, they can resolve any interference, so that the whole supply chain runs without major problems. The organisation of transport processes consists of several phases, which are an integral part of the whole process. Properly trained staff, knowledge of the transport market and the needs of the customer are essential for a company to function properly. Thanks to these three components, a company can offer services at the highest level. This work aims to develop a scheme of the transport process on the international market and also identify problems occurring in the organisation of transport processes. Some solutions to existing problems are also proposed.